2005
DOI: 10.1128/aem.71.11.6947-6953.2005
|View full text |Cite
|
Sign up to set email alerts
|

Iron Uptake Mechanisms in the Fish Pathogen Tenacibaculum maritimum

Abstract: We present here the first evidence of the presence of iron uptake mechanisms in the bacterial fish pathogen Tenacibaculum maritimum. Representative strains of this species, with different serotypes and origins, were examined. All of them were able to grow in the presence of the chelating agent ethylenediamine-di-(o-hydroxyphenyl acetic acid) (EDDHA) and also produced siderophores. Cross-feeding assays suggest that the siderophores produced are closely related. In addition, all T. maritimum strains utilized tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 53 publications
5
36
0
Order By: Relevance
“…The homogeneity of Tenacibaculum maritimum facilitates the use of the miniaturized systems API ZYM and API 50CH for its identification (Bernardet & Grimont 1989, Pazos et al 1993, Bernardet et al 1994, Chen et al 1995, Ostland et al 1999, Avendaño-Herrera et al 2004b, 2005c. In fact, within the API ZYM gallery, the majority of isolates display a characteristic profile (positive results in the first 11 enzymatic reactions), whereas within the API 50CH not all T. maritimum strains were able to produce acid from any carbohydrate substrate.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The homogeneity of Tenacibaculum maritimum facilitates the use of the miniaturized systems API ZYM and API 50CH for its identification (Bernardet & Grimont 1989, Pazos et al 1993, Bernardet et al 1994, Chen et al 1995, Ostland et al 1999, Avendaño-Herrera et al 2004b, 2005c. In fact, within the API ZYM gallery, the majority of isolates display a characteristic profile (positive results in the first 11 enzymatic reactions), whereas within the API 50CH not all T. maritimum strains were able to produce acid from any carbohydrate substrate.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Avendaño-Herrera et al (2005c) have demonstrated that this bacterium, regardless of its serotype, grows and multiplies in the presence of the chelating agent ethilenediamine-di-(o-hydroxyphenyl acetic acid) (EDDHA) using at least 2 different systems of iron acquisition. One mechanism involves the production of an unidentified siderophore, which is neither a phenolate nor a hydroxamate type, as demonstrated by the chromoazurol S (CAS) agar (Fig.…”
Section: Virulence Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics and reagents were from Sigma (St. Louis, MO). LB broth (tryptone, 10 g; yeast extract 5 g; NaCl, 10 g; glucose, 1 g; double-distilled water [ddH 2 O], 1 liter) (5), Bacto brain heart infusion (BHI) broth, chromoazurol S (CAS) broth (58), and Trypticase soy broth (TSB) were used routinely. When required, media were supplemented with 1.5% agar, 5% sucrose, colistin sulfate (Col) (12.5 g/ml), ampicillin (Amp) (100 g/ml), chloramphenicol (Cm) (25 g/ml), kanamycin (Km) (50 g/ml), FeSO 4 (150 M) (Sigma), or 2,2=-dipyridyl (150 M) (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…These siderophore mechanisms of iron acquisition have been linked to the virulence of different fish bacterial pathogens, such as Vibrio anguillarum (Listonella anguillarum) (38,73), Aeromonas salmonicida (24,27), Photobacterium damselae subsp. piscicida (13), Edwardsiella tarda (25), and Tenacibaculum maritimum (2). Direct iron uptake systems from host proteins rely on the interaction between specific microbial receptors and host transferrin or heme-containing compounds (31,41) and often involve bacterial hemolytic or proteolytic activity (10).…”
mentioning
confidence: 99%